La forêt guyanaise, entre valorisation et protection des ressources écosystémiques - André Calmont (VertigO)
Forests in French Guiana form an extremely complex ecosystem and have a wealth of flora and fauna of great diversity. During a long time, the exploitation of resources inside and outside the ecosystem was insignificant and was never considered in a sustainable development framework. However, as the population trebled over the last thirty years, the pressure of human activities on the forest environment has become significant, through timber production, hunting, gathering, agriculture, the use of biomass for energy purposes or furthermore gold mining. The awareness to potential risks on environmental biodiversity in an encouraging international atmosphere, has led public authorities to take a number of measures, regulatory, of sustainable management, and above all, in establishing a network of natural protected areas, such as a new National Park, called “The French Guiana Amazonian Park”.